Pengungkapan Tanggung Jawab Sosial Perusahaan Pada Tipe Perusahaan Di Indonesia - Eko Putri Setiani (Universitas Trunojoyo Madura, 2020)
This study aims to analyze the level of CSR disclosure in sustainability report and to analyze the comparison between GRI categories in high profile and low profile companies. The unit of analysis in this study are 34 companies that have published sustainability report. This research used content analysis method and the data are analyzed using descriptive statistic. The results of this study indicate that the average level of CSR disclosure of high profile companies is higher than low profile companies. The Economic category (EC) and Labor Practices and Decent Work sub-category (LA) are the categories with the highest disclosure rates in both high profile and low profile companies. In the Environmental category (EN), high profile companies do much higher disclosure than low profile companies. In the social category with sub category of Society (SO) and Product Responsibility (PR), there is no significant disclosure difference between high profile and low profile companies. The sub-category of Human Rights (HR) is the lowest-average category of disclosure in both high profile and low profile companies.